Insights gained from two decades of intensive monitoring: hydrology and nitrate export in a tile-drained agricultural catchment - Bauwe, Andreas; Lennartz, Bernd (Frontiers in Water, 2024)
Nitrate (NO3−) export from agricultural land poses an ongoing threat to both inland and coastal waters. Experimental studies investigating the hydrology-NO3−-export mechanisms require long-term data to identify reliable causal relationships. In this study, utilizing a 23-year continuous dataset with a high temporal resolution (daily to twice a week), we aim to identify potential drivers for NO3-losses and assess the impact of nitrogen (N) soil surface budgets on NO3-export. A drainage plot (4.2 ha) and a ditch catchment (179 ha) were fully equipped to register hydrological parameters, including water sample collection. Mean annual NO3−-N concentrations (loads) for the drainage plot and the ditch catchment were 9.4 mg l−1 (20.6 kg ha−1) and 6.0 mg L−1 (20.9 kg ha−1), respectively. Annual discharge was closely positively correlated with annual NO3-losses, highlighting the significant influence of prevailing weather and, consequently, hydrologic conditions on NO3-export rates. The majority of the annual NO3−-load was exported during winter (56% at the drainage plot, 51% at the ditch catchment), while the rest was exported during spring (28, 29%), summer (9, 9%) and fall (7, 11%). We could not find any direct relationships between N soil surface budgets and NO3-losses. Putting all results together, it can be concluded that agricultural activities for many decades resulted in high soil N stocks, which determined the general high NO3−-N concentration levels. Nevertheless, temporal NO3-export dynamics during the last two decades were clearly driven by hydro-meteorological conditions, nearly independently of land management and N soil surface budgets on the fields.